Upland rice breeding progress in Amapá State, Brazil - Atroch, André Luiz; Morais, Orlando Peixoto de; Rangel, Paulo Hideo Nakano; Castro, Emílio da Maia de (Pesquisa Agropecuaria Brasileira, 1999)
The upland rice (Oryza sativa L.) program progress in Amapá State, Brazil, is evaluated for grain yield, flowering period, plant height, lodging, disease resistance and grain type in lines from seven advanced and five preliminary tests conducted at Embrapa-Centro de Pesquisa Agroflorestal do Amapá (CPAF-AP) Experimental Station, during 1990/91 to 1995/96 crop seasons. Grain yield average annual gain of 83.0 kg/ha during the period is significant using t test at 1% level of probability, corresponding to 3.5% of annual increase in yield. Among the evaluated lines the CNA 6843-1, CNA 8386, CNA 8394, CNA 8170 and CNA 8441 were superior for the characters considered. CNA 6843-1 and CNA 7706, especially, showed remarkable improvement for lodging resistance and grain quality, two of the majors rice problems in Amapá. Theses results reinforce the collaborative rice breeding program strategy developed by the research institutions from the North and others regions of Brazil, based on a collaborative program by breeders that share their results from areas with similar conditions.